Research on the mechanical model of cord-reinforced air spring with winding formation - Cheng Yu-qiang (De Gruyter, 2021)
In this article, the parametric model for the stiffness characteristic and burst pressure of cord-reinforced air spring with winding formation is developed. Based on the non-geostrophic winding model and the assumption of cord cross-stability, the cord winding trajectory model of the capsule is established. Then, the anisotropic and nonlinear mechanics model of the capsule with complex cord winding trajectory variation characteristics is constructed by the classical thin-shell theory. The capsule state vector is solved by the extended homogeneous capacity precision integration method. Due to the complex coupling relationship between the capsule state vector and the internal air pressure, the stiffness characteristic is solved by the iterative integration method. The burst pressure of the air spring is solved by the Tsai–Hill strength theory. Eventually, the accuracy and reliability of the proposed method are verified by the experimental results. The effects of the material properties, winding parameters, and geometric structure parameters on stiffness characteristics and burst pressure are discussed. The results of this article provide an important theoretical basis for the performance design of cord-reinforced air springs with winding formation.